(3OQGSGJ eJbOeI aj GdJShjbs - (3Cjef Ydj(B, (3YeQs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3GdJShjb ef NdGd GdYdGbGJ HGdYedGA(B- (3GdJMOjGJ GdJShjbjI GdJj JhGLg efXeGJ GdCYeGd(B- (3SjGSI GdefJL aj Gdeaghe GdJShjbj(B- (3GdJcJdGJ GdGbJUGOjI GdYGdejI(B- (3GdSjGSGJ GdGbJUGOjI hGdbOQI GdJfGaSjI ddefJLGJ GdeUQjI(B- (3GdJLGQI GdGdcJQhfjI(B- (3HYV GdEJLGgGJ GdMOjKI aj GdJShjb(B- (3EOGQI GdCReGJ GdJShjbjI hehGLgI GdeTcdGJ(B- (3efWbI GdJLGQI GdMQI GdYQHjI(B- (3efXeI GdJLGQI GdYGdejI(B- (3OhQ COhGJ GdJShjb aj JZjjQ Sdhc GdeSJgdc(B- (3EYGOI gfOSI GdYedjGJ GdJShjbjI ceONd dJWhjQ COGA GdefXeGJ GdeUQjI hGdEfWdGb dRjGOI GdUGOQGJ(B- (3GdGJUGdGJ GdaYGdI aj eLGd GdJShjb(B- (3WQb GdJZdja GdMOjKI(B- (3fUGFM eQHMI ddeUOQjf(B- (3GdMcheI GdEdcJQhfjI(B- (3cja JDKQ aj Sdhc GdeSJgdc HWQjbI GjLGHjI(B- (3GdJShjb GdTHcj(B- (3GdJShjb GdGdcJQhfjs
(3GdeQGLY U(B.380s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs